The presence of liver cirrhosis is a strong negative predictor of survival for patients admitted to the intensive care unit – Cirrhosis in intensive care patients - Kubesch, Alica; Peiffer, Kai Henrik; Abramowski, Hannes; Dultz, Georg; Graf, Christina; Filmann, Natalie; Zeuzem, Stefan; Bojunga, Jörg; Friedrich-Rust, Mireen (Zeitschrift für Gastroenterologie, 2021)
Background and Aims Liver cirrhosis is a systemic disease that substantially impacts the body’s physiology, especially in advanced stages. Accordingly, the outcome of patients with cirrhosis requiring intensive care treatment is poor. We aimed to analyze the impact of cirrhosis on mortality of intensive care unit (ICU) patients compared to other frequent chronic diseases and conditions.Methods In this retrospective study, patients admitted over three years to the ICU of the Department of Medicine of the University Hospital Frankfurt were included. Patients were matched for age, gender, pre-existing conditions, simplified acute physiology score (SAPS II), and therapeutic intervention scoring system (TISS).Results A total of 567 patients admitted to the ICU were included in the study; 99 (17.5 %) patients had liver cirrhosis. A total of 129 patients were included in the matched cohort for the sensitivity analysis. In-hospital mortality was higher in cirrhotic patients than non-cirrhotic patients (p < 0.0001) in the entire and matched cohort. Liver cirrhosis remained one of the strongest independent predictors of in-hospital mortality (entire cohort p = 0.001; matched cohort p = 0.03) along with dialysis and need for transfusion in the multivariate logistic regression analysis. Furthermore, in the cirrhotic group, the need for kidney replacement therapy (p < 0.001) and blood transfusion (p < 0.001) was significantly higher than in the non-cirrhotic group. Conclusions In the presented study, liver cirrhosis was one of the strongest predictors of in-hospital mortality in patients needing intensive care treatment along with dialysis and the need for ventilation. Therefore, concerted efforts are needed to improve cirrhotic patients’ outcomes, prevent disease progression, and avoid complications with the need for ICU treatment in the early stages of the disease.
Keywords: cirrhosis; intensive care unit (ICU); decompensation; predictors; MELD